Stock Returns and Trading Volume Relationship of the Nigerian Banking Sector: An Empirical Assessment - Ugwu, Ugwu; ., Sule; ., Kehinde Oluwatoyin; ., Emerole; ., Gideon Ahamuefula (Journal of Social and Development Sciences, 2011)
This study assessed the relationship between stock returns and trading volume, using daily data of some Nigerian Banking Sector Stocks. It further checked for both the contemporaneous and causal relationship between stock return and trading volume utilizing data covering ten (10) companies from the Banking Sector. Six hundred and nineteen to seven hundred and six (619-706) observations for a period of thirty â€“ six months (36) from 1st March, 2004 to 28th February, 2007, were empirically tested with the Granger-Causality tests. This determined if the Wall Street adage which says, â€œIt takes volume to make pricesâ€ was true in the Nigerian Banking Sector. Using the daily data, we first found a negative relation between and absolute value of price changes (return) and price changes itself in the Nigerian Banking Stocks. However, the results from the Granger-Causality test failed to find strong evidence on stock price changes leading volume. This was contrary to evidence reported by study on developed markets but consistent with previous result from the Latin American Market which is an emerging market like that of Nigeria. In fact, in all the ten banks studied, volume seems to lead stock price changes. Thus, we concluded that these set of emerging markets with different institutions and information flows than the developed markets, do not present similar stock/return-volume relationship to the preponderance of studies employed U.S data. The implication of these results was that differences in institutions and information flows in the set of emerging markets are important enough to affect the valuation process of equity securities and warrant further analysis.